Ordenamento territorial como estratégia de desenvolvimento de municípios de pequeno porte no Brasil - Jeferson Tavares (Cidades, Comunidades e Território)
Territorial planning as a strategy for urban and regional planning in small cities in Brazil can answer to the contradictions arising from productive restructuring and represent an alternative of development. Based on this argument, the text aims to problematize experiences of regional arrangements in Brazilian city systems that occur in a municipalist context reinforced by the Federal Constitution of 1988. This context weakens small cities that are not inserted in the traditional dynamics of space production derived of productive restructuring. To explore alternatives, the theoretical foundation of the analysis is based on the different meanings of the term ‘territory’ because they contribute to the understanding of contemporary planning movements. Methodologically, we start with a bibliographic review on the models used in territorial planning, called ‘territorial associations’ in Brazil, and position them in national and international criticism. As a discussion, it problematizes some experiences of territorial associations in city systems, identifying their particularities, contradictions and convergences. This analysis allows us to conclude that planning based on territorial evidence can represent an important support in the formulation of public policies and guarantee planning alternatives, especially in small cities.